Successful use of the interleukin-17A inhibitor (ixekizumab) in the treatment of psoriatic arthritis - A. M. Dadalova; E. A. Vasilenko; R. R. Samigullina; V. I. Mazurov (Современная ревматология)
Psoriatic arthritis (PsA) is a chronic immune-mediated disease from a group of spondyloarthritis, which is characterized by damage to the musculoskeletal system with a wide range of different clinical manifestations and is usually associated with psoriasis. Activation of the interleukin (IL) 23/IL17 axis plays a key role in the pathogenesis of PsA and psoriasis. When non-steroidal and synthetic disease-modifying antirheumatic drugs are insufficiently effective, biological drugs are recommended. In recent years, there have been considerable advances in PsA treatment with tumor necrosis factor-α (IFN-α) inhibitors and IL-12/23 inhibitors. However, in some cases, this therapy fails to provide the desired effect and a search for new treatments for PsA seems to be an urgent task. The paper desctibes a clinical case demonstrating the efficacy of the IL17A inhibitor ixekizumab in a patient with high PsA activity and recurrent uveitis in both eyes. Ixekizumab therapy resulted in positive changes as the reduced severity of articular syndrome and psoriasis and normalization of acute phase parameters. Assessing the activity of PsA over time when using ixekizumab during a year showed an average decrease in ESR from 72 to 19 mm/h, in CRP from 162.1 to 0 mg/L, BSA from 51 to 0.25%, PASI from 43. 6 to 0, DAPSA from 78.2 to 2, ASDAS-SRB from 5.11 to 1.12, BASDAI from 4.85 to 1, BASFI from 5.3 to 0.7, BASMI from 5.0 to 2.6, MASES from 6 to 0, LEI from 2 to 0, SPARCC from 6 to 0, and NAPSI from 28 to 8. Thus, this clinical case is an example of successful treatment with the IL17 inhibitor ixekizumab for PsA with recurrent uveitis in the patient who has previously received three drugs from the TNFα group without any effect.